UATV: Ukraine’s Voice on the Information Battlefield - Dzholos, Oleh (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
This article describes the important role that international broadcasting has played since its inception in promoting state sovereignty and reducing foreign propaganda in information warfare, with a particular focus on Ukraine. The author provides a thorough overview of the historical development of international broadcasting in Ukraine and how it has evolved since the Russian annexation of Crimea, the occupation of Donbass, and the full-scale invasion. While research in the field has been dominated by analyses of ‘traditional’ or ‘mainstream’ media, such as radio and television, this article analyses how the Ukrainian International Broadcasting UATV English on YouTube and Facebook social media platforms have functioned over the first six months since Russia’s full-scale invasion of Ukraine. The author finds UATV effective in restricting the aggressor’s propaganda in the Western media space, pointing out the lack of activity in Asia-Pacific and the strategic importance of ensuring the presence of Ukrainian International Broadcasting in the Asia-Pacific region.